Numerical simulation of axial shortening distance in friction stud welding of aluminium/mild steel joints. (2021) - Rajesh Jesudoss Hynes, N.; Raja, S.; Angela Jennifa Sujana, J.; Benita, B.; Sankaranarayanan, R.
Abstract: The execution of numerical simulation in friction-stud welding technique comprises of complex steps involving the thermo-mechanical phenomena along with metallurgical modifications within the materials. It is explored that welded component's mechanical properties mainly depend on the inter-metallic bonding between the dissimilar metals and hence axial shortening distance plays a key role in the determination of the strength of the weld. Owing to its significance, numerical model is established based on finite element to predict the actual axial shortening distance accurately. The validation of the numerical model was accomplished through comparing the numerical predicted data with actual experimental data. Through this validation, axial shortening distance can be predicted for aluminium and mild steel combination of dissimilar material at the enhanced level of accuracy. These validation inferences are essential sources for ensuring the quality level at the region of welding. In addition to S that, numerical simulation results related to stress, thermal gradient plots, strain and thermal flux are furnished in the present work.